Human footprint everything you will eat, use, wear, buy, and throw out in your lifetime - Kirk, Ellen, author (Washington, D.C. : National Geographic, 2010)
"What's your human footprint? Well, it's 13,056 pints of milk; 28,433 showers; 12,888 oranges; 14,518 candy bars; 43,371 cans of soda; and $52,972 worth of clothes, all in one lifetime. And that's just a fraction of the mountain of stuff you'll consume. Think of that times six billion other footprints. Makes you want to step more lightly on the Earth!"--P. [4] of cover.
OSLIS\Gale Nat Geo eBooks(2/2/23).
"The book is based on the Preserve our Planet National Geographic Channel presentation, Human footprint"--P. 32.
Includes bibliographical references.
Description based on print version record.
Keywords: Human ecology -- United States -- Juvenile literature; Nature -- Effect of human beings on -- United States -- Juvenile literature; Consumption (Economics) -- Environmental aspects -- United States -- Juvenile literature; Consumption (Economics) -- Social aspects -- United States -- Juvenile literature; Population -- Environmental aspects -- Juvenile literature; Lifestyles -- Social aspects -- United States -- Juvenile literature; Nature -- Effect of human beings on; Human ecology; Sustainable living; Electronic books- OSLIS; Electronic books